The idea is not enough: The role of self-efficacy in mediating the relationship between pull entrepreneurship and founder passion – a research note. (December 2015) - Dalborg, Cecilia; Wincent, Joakim
This research note demonstrates that self-efficacy is important for understanding why an attractive idea may lead an entrepreneur to develop passion. Drawing upon a survey of 103 respondents, we find that self-efficacy mediates the influence of pull entrepreneurship on founder passion suggesting that being pulled toward opportunities to start a business is not directly required for entrepreneurial passion to develop. Instead, pull entrepreneurship increases self-efficacy and assists the individual to develop the skills typical of an entrepreneur. This instills individual self-efficacy beliefs, which in turn are prerequisites for passion to grow. As such, this research uncovers a skill-based explanation of how founder passion develops.